(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Purpose of the study. To study the contribution of IL-17F (rs763780) and IL23R (rs11209026) gene polymorphisms to the development of aplastic anemia. Methods. The material for clinical and laboratory studies in the work were patients with AA (n=86) who sought diagnostic help and subsequent inpatient examination at the republican specialized Scientific and Practical Medical Center of Hematology (RSSPMCH, Tashkent) from 2019 to 2023. Patients with AA ranged in age from 18 to 79 years, while the median age was 40.8±1.8 years. The diagnosis was made taking into account clinical and laboratory data. A four milliliter peripheral blood sample was taken from all participants to study single nucleotide polymorphisms IL-23R (rs11209026; G1142A) and IL-17F (rs763780; A7488G) using polymerase chain reaction of restriction fragment length polymorphism (PCR-PDRF). The samples were stored at a temperature of -80 °C until DNA was isolated. The results were statistically processed using the PC application package "OpenEpi 2009, Version 2.3". Conclusions. The results obtained by analyzing differences in polymorphic loci of the IL17F (His161Arg) gene in the main group of patients with AA compared with the control showed a statistically significant association between His/Arg heterozygote and the risk of AA. Moreover, the detected tendency to increase the frequency of the weakened Arg allele by 2.1 times and His/Arg heterozygote by 2.2 times in the group with severe AA, as well as to increase the frequencies of the weakened Arg allele by 2.4 and His/Arg heterozygote by 2.6 times in the group of patients with superheavy AA allows them to be considered as genetic predictors of AA weighting. The results of the study of IL23R (G/A) genetic polymorphism indicate the absence of independent associative links with an increased risk of AA development and severity.